2021
DOI: 10.3390/jcm10030380
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatic Artery Stenosis in Liver Transplant Patients Using Drug-Eluting versus Bare-Metal Stents

Abstract: Hepatic artery stenosis after liver transplant is often treated with endovascular stent placement. Our institution has adopted use of drug-eluting stents, particularly in small-caliber arteries. We aimed to compare patency rates of drug-eluting stents vs. traditional bare-metal stents. This was a single-institution, retrospective study of liver transplant hepatic artery stenosis treated with stents. Primary patency was defined as time from stent placement to resistive index on Doppler ultrasonography (<0.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
0
1
5
Order By: Relevance
“…When excluding thrombosis, our complication rate of 9.5% (2/21) following hepatic artery angioplasty and/or stenting was similar to previously reported rates of 5.3-12% [5,8,[10][11][12]. When comparing the rates of hepatic artery thrombosis following angioplasty and/or stenting for HAS, our rate of 19% (4/21) was slightly lower than previously reported rates of 27-28% [20][21]. Previous retrospective reviews reported an increase in RI between 0.1 to 0.2 following direct hepatic artery interventions, which is concordant with the + 0.11 change in RI within our HAI treatment group [8,9].…”
Section: Previous Studies On Direct Hepatic Artery Interventions Cons...supporting
confidence: 87%
“…When excluding thrombosis, our complication rate of 9.5% (2/21) following hepatic artery angioplasty and/or stenting was similar to previously reported rates of 5.3-12% [5,8,[10][11][12]. When comparing the rates of hepatic artery thrombosis following angioplasty and/or stenting for HAS, our rate of 19% (4/21) was slightly lower than previously reported rates of 27-28% [20][21]. Previous retrospective reviews reported an increase in RI between 0.1 to 0.2 following direct hepatic artery interventions, which is concordant with the + 0.11 change in RI within our HAI treatment group [8,9].…”
Section: Previous Studies On Direct Hepatic Artery Interventions Cons...supporting
confidence: 87%
“…When excluding thrombosis, our complication rate of 9.5% (2/21) following hepatic artery angioplasty and/or stenting was similar to previously reported rates of 5.3–12% [ 5 , 8 , 10 12 ]. When comparing the rates of hepatic artery thrombosis following angioplasty and/or stenting for HAS, our rate of 19% (4/21) was slightly lower than previously reported rates of 27–28% [ 20 , 21 ]. Previous retrospective reviews reported an increase in RI between 0.1 to 0.2 following direct hepatic artery interventions, which is concordant with the + 0.11 change in RI within our HAI treatment group [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Имплантация стентов в зону сужения ПА после ТП является безопасным и эффективным вмешательством. Стенты с лекарственным покрытием (СЛП) после ТП показывают лучшие результаты по проходимости в сравнении с голометаллическими стентами (ГМС) [14,17]. D. Fleck et al сообщают о том, что проходимость СЛП в печеночной артерии составляет 62% через 1, 2 и 3 года.…”
Section: Discussionunclassified
“…А проходимость ГМС составляет 65%, 53% и 45% через те же сроки соответственно. Выживаемость трансплантата печени после имплантации СЛП составляет 100% через 1, 3 и 5 лет, а после стентирования ГМС через те же сроки составляет 97%, 87%, 83% соответственно [17].…”
Section: Discussionunclassified
See 1 more Smart Citation